Necessity of adjuvant concurrent chemo-radiotherapy in D2-resected LN-positive gastric cancer - Yu, Jeong Il; Lim, Do Hoon; Lee, Jeeyun; Kang, Won Ki; Park, Se Hoon; Park, Joon Oh; Park, Young Suk; Lim, Ho Yeong; Kim, Seung Tae; Lee, Su Jin; Kim, Sung; Sohn, Tae Sung; et al. (Radiotherapy and Oncology, 2018)
Background and purpose: To investigate the role of adjuvant concurrent chemo-radiotherapy (CCRT) by analyzing the outcomes of adjuvant CCRT versus chemotherapy alone (CA) in patients with D2-resected gastric cancer with lymph node (LN) metastasis. Materials and methods: Patients with gastric cancer from the institutional registry who underwent curative D2 and R0 resection from December 2004 to January 2013 followed by adjuvant CCRT or CA and demonstrated pathologically confirmed LN metastasis without distant metastasis were included in the study. Results: A total of 1633 patients were included (909 patients in the adjuvant CCRT group and 724 patients in the CA group), and median follow-up was 65.4 months (range, 3.9–141.7 months). There was a significant difference in age (p < 0.0001), Lauren's classification (p = 0.02), number of LN metastases (p < 0.0001), and pN stage (p < 0.0001) between the CCRT and CA groups. During follow-up, recurrence was detected in 419 (25.7%) of patients overall, 236 (26.0%) in the CCRT group, and 183 (25.3%) in the CA group. Recurrence-free survival (RFS) was not significantly different between the CCRT and CA groups in univariable analysis (p = 0.92). After adjustment, pT/pN stage and perineural invasion showed statistical significance in multivariable Cox regression analysis; however, RFS was significantly higher in the CCRT group (p = 0.03, hazard ratio 0.801, 95% confidence interval 0.658–0.975). Conclusions: The adjusted RFS was significantly higher in the CCRT group than the CA group in patients with D2 resected LN metastatic gastric cancer.
Keywords: Adult; Aged; Chemoradiotherapy, Adjuvant; Chemotherapy, Adjuvant; Female; Humans; Lymph Node Excision; Lymphatic Metastasis; Male; Middle Aged; Neoplasm Recurrence, Local; Radiotherapy, Adjuvant; Stomach Neoplasms; Young Adult; Adjuvant; Chemotherapy; Concurrent chemo-radiotherapy; Gastric cancer; Recurrence